Experimental Evaluation of Construction Waste and Ground Granulated Blast Furnace Slag as Alternative Soil Stabilisers - Hasan, U.; Chegenizadeh, Amin; Budihardjo, Arief; Nikraz, Hamid (2016)
© 2016 Springer International Publishing Switzerland In this study, the effect of ground granulated blast furnace slag (GGBFS) and recycled construction waste (CW) on bentonite clay stabilisation were investigated. The unconfined compressive strength (UCS) of specimens was evaluated with different combinations of GGBFS and CW over various curing periods. A series of micro analysis tests consisting of scanning electron microscope, energy dispersive spectrometer and X-ray diffraction were also conducted to determine the microstructural arrangement and mineralogical effect of the stabilisation treatment. The UCS results showed an increment in strength after introduction of GGBFS and CW and the longer curing period produced more pronounced results. The optimum additive ratio was calculated as 5 % of slag and 20 % of construction waste under all curing conditions. The micro analytical results also indicated formation of structural bonds between admixtures and bentonite in stabilised specimens, as slag crystals and bentonite particles were observed to occupy the cavities and vesicles on the construction waste grains. However, the experimental data shows that the strength improvement is not significant with the addition of only construction waste.